Pengaruh Green Leadership dan Budaya Organisasi Terhadap Lingkunga Siswa - Amalin Dwi Annisa Putri; Utik Bidayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the influence of green leadership and organizational culture on students' environmental behavior at SMA Muhammadiyah 1 Prambanan, both partially and simultaneously. The method used is descriptive analysis with a quantitative approach. Data were collected through questionnaires with a total of 100 students selected using a simple random sampling technique. Data analysis was carried out using multiple linear regression with the help of the SPSS program. The results of the study indicate that green leadership has a positive and significant effect on students' environmental behavior. Organizational culture is also proven to have a positive and significant effect on students' environmental behavior. Simultaneously, green leadership and organizational culture have a significant effect on students' environmental behavior. This study shows that the implementation of environmentally oriented leadership and an organizational culture that supports environmental awareness play an important role in shaping students' environmentally friendly behavior at school.